Influence of Various Chemical Surface Treatments, Repair Materials, and Techniques on Transverse Strength of Thermoplastic Nylon Denture Base - Ghassan Abdul-Hamid Naji (International Journal of Dentistry)
The process of repairing the fractured nylon denture bases and addition of acrylic teeth to the previously worn nylon denture bases has not been widely studied. This study aims to assess the transverse strength of nylon denture bases repaired by various resin materials, different curing techniques, and types of surface treatments. Materials and Methods. One hundred fifty thermoplastic nylon denture base samples were fabricated using plastic patterns measuring 65 × 10 × 2.5 mm (length, width, and thickness, respectively). These samples were then divided into three equal groups. Fifty samples were repaired by microwave heat-polymerization, fifty samples were repaired using the Ivomate autopolymerization, and the other fifty were repaired using light-polymerized acrylic resin. Each of these three groups was further divided into five subgroups of ten samples based on the type of surface treatment. The samples in the control group did not undergo any surface treatment, and the other four groups were chemically surface treated with monomer, acetone, ethyl acetate, and isopropanol, respectively. A three-point bending test was used to calculate the transverse strength values of the samples. Fourier transform infrared (FTIR) analysis was conducted to determine the component of functional groups between the polyamide nylon base and poly(methyl-methacrylate) PMMA repair materials. A polarizing microscope was utilized to investigate the mode of failure at the fracture surfaces. Results. The collected data were analyzed with one-way ANOVA and Sidak’s multiple comparison test to show the differences among different groups. For surface treatments, the highest transverse strength values were obtained by monomer-treated samples (18.29 N/mm2); however, the lowest values were obtained in non-surface treated samples (5.58 N/mm2). While for repair techniques, the highest transverse strength values were obtained by microwave processing, followed by Ivomate and then the light-cured polymerization. The means were found to be significant (p<0.001). FTIR analysis shows the presence of hydrogen bonding which is due to the ester and amid groups which enhance the bond strength of the surface-treated samples. The interface of the polarizing microscope images revealed a cohesive fracture within repair materials rather than the adhesive nature. Conclusion. The microwave-polymerized resin was considered as the most effective repair technique along with monomer chemical etchant which creates a tight adhesion between PMMA and nylon denture base in comparison to other groups.